Importance of genetics as a science in relation to the COVID-19 pandemic - Sanchez-Castro, Enrique Eduardo (2020)
The current COVID-19 pandemic has become a major global public health problem with almost one and a half million cases and tens of thousands of deaths until now. Genetics is playing a leading role in the identification, management and treatment of diseases. This article details the importance of genetics as a science to face the global threat of COVID-19, from different approaches. The contributions that genetics have had and will continue to have in the identification of the new SARS-CoV-2 virus, in the development of new diagnostic techniques, in the prevention of infections and development of severe symptoms, as well as in the design of vaccines and in the proposal and evaluation of treatments for COVID-19.